Immunoblotting in the diagnosis of culture negative endocarditis caused by streptococci and enterococci. Issue 12 (December 1995) - Burnie, J P; Clark, I
Abstract : AIM--To improve the diagnosis of culture negative endocarditis by diagnosing cases due to streptococci and enterococci. METHODS--Serum samples were immunoblotted against extracts of the commonest streptococci and enterococci. They were selected from patients with a cardiac murmur, persistent pyrexia and at least three negative blood cultures. The presence of patterns of endocarditis species specific antigenic bands was measured and correlated with clinical outcome. RESULTS--Negative serology was found in 28 patients where the diagnosis of endocarditis was rejected or, if proved, staphylococcal, yeast, Gram negative, systemic lupus erythematosus, due to Q fever or Chlamydia psittaci or nonbacterial thrombotic. Positive serology was found in 27 of the 34 patients where the response to antibiotics suggested streptococcal or enterococcal infection. In 22 of these there was objective evidence of endocarditis. Positive serology was also found in three of four further patients with vegetations at necropsy. CONCLUSION--The identification of patterns of antibody response on immunoblotting can be used to make a specific diagnosis of streptococcal or enterococcal endocarditis in the absence of positive blood cultures.